POTENSI PENGEMBANGAN PROPERTI DI SINGKAWANG, KALIMANTAN BARAT - Hengky Hengky; Regina Suryadjaja; Suryono Herlambang (Jurusan Arsitektur dan Perencanaan, 2026)
Singkawang City is one of the cities in West Kalimantan Province that holds a strategic position and plays an important role in supporting regional economic growth. This study aims to examine the development and current condition of the property market in Singkawang City, including growth trends, types of properties developed, and the direction of urban development. The research employs a descriptive method with both qualitative and quantitative approaches, supported by spatial analysis. Research data were obtained from primary data such as field surveys, as well as secondary data sourced from government institutions, literature studies, and digital mapping using Google Maps and QGIS. The research variables include the location and spatial distribution of properties, types and functions of developed properties, growth in property supply, market demand, and the direction of area development. The analysis refers to the Appraisal Institute (2020), which states that property development and value are strongly influenced by location, accessibility, the intensity of economic activities, and their relationship with activity centers and infrastructure networks. These factors determine land use patterns and the direction of urban development. The results indicate that property development in Singkawang City is driven by the trade, service, and tourism sectors, supported by its strategic geographical position and infrastructure development. The highest increase in property supply occurred in 2022, with 16 new properties added. The property type experiencing the most significant growth was cafés, totaling 38 units. Furthermore, new property development tends to expand toward the North Singkawang area. In conclusion, Singkawang City has significant potential for property development and plays an important role in promoting balanced regional development. Keywords: Singkawang, property development, West Kalimantan, growth centers. Abstrak Kota Singkawang merupakan salah satu kota di Provinsi Kalimantan Barat yang memiliki posisi strategis dan berperan penting dalam mendukung pertumbuhan ekonomi regional. Penelitian ini bertujuan untuk mengetahui perkembangan dan kondisi pasar properti di Kota Singkawang, meliputi tren pertumbuhan, jenis properti yang berkembang, serta arah pengembangan wilayah. Metode penelitian yang digunakan adalah metode deskriptif dengan pendekatan kualitatif dan kuantitatif, yang didukung oleh analisis spasial. Data penelitian diperoleh melalui data primer seperti survei serta data sekunder yang bersumber dari instansi pemerintahan, studi literatur, dan pemetaan digital menggunakan Google Maps dan QGIS. Variabel penelitian meliputi lokasi dan sebaran properti, jenis dan fungsi properti yang berkembang, pertumbuhan supply properti, permintaan pasar, serta arah pengembangan wilayah. Analisis dilakukan dengan mengacu pada Appraisal Institute (2020) yang menyatakan bahwa perkembangan dan nilai properti sangat dipengaruhi oleh lokasi, aksesibilitas, intensitas aktivitas ekonomi, serta keterkaitannya dengan pusat kegiatan dan jaringan infrastruktur. Faktor-faktor tersebut menentukan pola pemanfaatan lahan dan arah pengembangan kawasan perkotaan. Hasil penelitian menunjukkan bahwa perkembangan properti di Kota Singkawang didorong oleh sektor perdagangan, jasa, dan pariwisata, yang diperkuat oleh posisi geografis strategis serta perkembangan infrastruktur. Peningkatan supply properti tertinggi terjadi pada tahun 2022 sebanyak 16 properti baru, dengan jenis properti yang mengalami pertumbuhan terbesar berupa kafe sebanyak 38 unit. Arah pengembangan properti baru cenderung mengarah ke wilayah Singkawang Utara. Kesimpulannya, Kota Singkawang memiliki potensi perkembangan properti yang signifikan dan berperan dalam mendorong pemerataan pembangunan wilayah.